Identifikasi Gangguan Reproduksi pada Ovarium Sapi Potong yang Mengalami Anestrus Postpartum Panjang (IDENTIFICATION OF REPRODUCTIVE DISRUPTION ON PROLONGED POSTPARTUM ANESTRUS BEEF COW OVARIES) - Rosadi, Bayu; Sumarsono, Teguh; Hoesni, Fachroerrozi (Jurnal Veteriner; Vol 19 No 3 (2018), 2018)
Postpartum anestrus is the major factor causing elongation of the calving interval and in consequense, lowering beef cow productivity.  Anestrus condition is closey related to inactive ovary condition.  The research was conducted to find out reproductive disorders in ovarian of beef cattle cow that underwent prolonged postpartum anestrus (more than 3 months). One hundred and fifty heads post partum anestrus cow were selected.  The  general body condition  were evaluated based on  Body Condition Score (BCS).  The types of reproductive disruption in ovary were determined by rectal palpation method. The cows observed had 2.0 to 3.2 (2.6 ± 0.7) in BCS. The result showed that 37.68% of prolonged postparum anestrus cow had ovarian disorders. The types of ovarian disoreders detected were hypofunction (19.32%), cystic follicle (8.21%), persistent corpus luteum (4.5%), atrophy (1.93%) and partial agenesis (0.97%).